PROVIDE ONGOING ASSISTANCE TO ORPHANS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, July 2015 Aids and donations to orphans and needy children should be given on a continuous basis and not only during the month of Ramadhan. That was the view of the founder of Rumah Anak Yatim Ummu Salamah Gerik Perak, Mufahuddin Abdul Razak, 48, when he received donations on behalf of the orphanage from the convoy organised by Universiti Sains Malaysia School of Distance Education (PPPJJ USM) recently.